Attagenus fasciatus (Thunberg) and Reesa vespulae (Milliron) (Coleoptera Dermestidae), two synanthropic pests new for Italy (notes on the insect pests of a spice factory) (Bollettino di zoologia agraria e bachicoltura, 2024)
During research carried out on the insect pests in a factory of spices and aromaticherbs located in the Bologna province (Emilia Romagna, Northern Italy), insectscollected in 1998-99 by light traps sited inside the building were identified. Aswell as other infestants, Attagenus fasciatus (Thunberg) and Reesa vespulae(Milliron) were found. These two dermestids had never previously been recordedin Italy, either on stored products or outdoors. Both species are well-known pestsfound in buildings, on stored food products and other goods, so they are becomingwidespread. A. fasciatus is widely distributed throughout the warmer regions ofthe world and was accidentally introduced, or is periodically re-imported, intovarious temperate countries by international trade. R. vespulae is a Nearcticspecies which has spread to several European and Asiatic countries for the samereason. Morphological notes useful for the identification of these dermestids andinformation about their biology and most frequently infested substrates arereported. In addition, a table listing the other main insects collected by light trapsin the above spice factory is provided.
Keywords: dermestids; spice factory; incidental introduction; Northern Italy